Palaeochiridiinae subfam. nov. (Arachnida: Pseudoscorpiones: Pseudochiridiidae) from mid-Cretaceous Burmese amber, with a description of new genus and species - Turbanov, Ilya S.; Kolesnikov, Vasiliy B.; Vorontsov, Dmitry D.; Shadrin, Danila S.; Vasilenko, Dmitry V.; Perkovsky, Evgeny E. (Zootaxa, 2025)
A new subfamily, genus and species of pseudochiridiid pseudoscorpions is described from mid-Cretaceous Burmese amber (Myanmar), including a detailed diagnosis and illustrations: Palaeochiridium insolitum gen. et sp. nov. (Arachnida: Pseudoscorpiones) is the first valid species of the family Pseudochiridiidae from Burmese amber. Diagnostic, biogeographic, paleohabitat and ecological features of this new species are presented and discussed, and are compared to the related extinct and extant species of this family.